Bidirectional associations between psychological distress and hearing problems: an 18-year longitudinal analysis of the British Household Panel Survey - Herr, Raphael; Bosch, Jos A.; Theorell, Töres; Loerbroks, Adrian (International journal of audiology, 2018)
Objective: Hearing problems are a significant public health concern. It has been suggested that psychological distress may represent both a cause and a consequence of hearing problems. Prospective data that allow testing such potential bi-directionality have thus far been lacking. The present study aimed to address this knowledge gap. Random (RE) and fixed effects (FE) panel regression models estimated the association of psychological distress (GHQ-12) and participant-reported hearing problems. Data from 18 annual waves of the British Household Panel Survey were used (n = 10,008). Psychological distress was prospectively associated with self-reported hearing problems in women (multivariable odds ratios (ORs) ≥1.44; one-year time lag ≥ 1.16) and men (ORs ≥ 1.15; time lag ≥ 1.17). Conversely, self-reported hearing problems were associated with increases in psychological distress in both sexes (OR ≥ 1.26; time lag ≥ 1.08). These associations were independent of the analytical strategy and of adjustment for sociodemographic variables, lifestyle factors, and measurement period. We present first evidence of a bidirectional association between psychological distress and self-reported hearing problems. These findings suggest that stress management interventions may contribute to the prevention of self-reported hearing problems, and, in turn, alleviating self-reported hearing problems may reduce psychological distress
Published online: 27 Jul 2018
Gesehen am 19.12.2019